2018
DOI: 10.1159/000489298
|View full text |Cite
|
Sign up to set email alerts
|

Signet Ring Carcinoma of the Appendix Presenting as Crohn’s Disease in a Young Male

Abstract: Primary signet ring cell carcinoma is a rare event in surgery. It looks like acute appendicitis and it is difficult to diagnose it on clinical grounds alone. The diagnosis is always confirmed by histopathology of a surgically removed appendix. A young man, 22 years old, presented with vomiting, diarrhea, and cramps in his abdomen without abdominal tenderness (mild abdominal discomfort in the right lower abdominal quadrant without signs of peritoneal irritation) during the previous month. The first endoscopic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Appendiceal carcinomas are found incidentally during surgery in cases of acute appendicitis, representing 1% of appendectomies (2). Appendiceal cancer presents with significant morphological diversity and is further classified into carcinoid (NET), mucinous cystadenocarcinoma, adenocarcinoma, GCC and signet ring cell tumors (2,3). Due to the fact that GCCs are discovered incidentally during routine appendectomy, there is a lack of a standardized classification system and discrepancies regarding specific reliable markers, such as Ki-67; this may lead to misdiagnosis and suboptimal treatment and surgical approaches (i.e., hemicolectomy or multivisceral resection).…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal carcinomas are found incidentally during surgery in cases of acute appendicitis, representing 1% of appendectomies (2). Appendiceal cancer presents with significant morphological diversity and is further classified into carcinoid (NET), mucinous cystadenocarcinoma, adenocarcinoma, GCC and signet ring cell tumors (2,3). Due to the fact that GCCs are discovered incidentally during routine appendectomy, there is a lack of a standardized classification system and discrepancies regarding specific reliable markers, such as Ki-67; this may lead to misdiagnosis and suboptimal treatment and surgical approaches (i.e., hemicolectomy or multivisceral resection).…”
Section: Discussionmentioning
confidence: 99%
“…However, the definitive diagnosis was SRCC-A. [15] This also indicated that caution must be taken to avoid misdiagnosis. Up to 40% of cases present with distant metastases to the peritoneum, liver, and/or ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…AMNs remain a rare clinical entity in IBD patients: to this date, current evidence relies on 22 [ 18 , 19 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] case reports and only 1 retrospective case–control study [ 14 ]. To our knowledge, this is the very first review of cases of AMN in IBD patients.…”
Section: Discussionmentioning
confidence: 99%